The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jvh.13030
|View full text |Cite
|
Sign up to set email alerts
|

Clinical noninvasive markers for antiviral therapy decision in chronic hepatitis B with alanine aminotransferase less than two times upper limit of normal

Abstract: Summary Liver biopsy is the reference method for antiviral therapy decision‐making in chronic hepatitis B (CHB) when alanine aminotransferase (ALT) is less than two times of upper limit of normal (<2ULN). Our aim was to explore noninvasive markers for antiviral therapy decision in CHB with ALT <2ULN. A total of 452 treatment‐naïve CHB patients with ALT < 2ULN who had undergone liver biopsy were analysed in this prospective multi‐centre study. If liver biopsy showed moderate or severe inflammation (histology ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Logistical regression showed that AST was a more stable and capable index of indicating liver inflammation grade than ALT. Chen SS and other authors also reported similar findings (25,26).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Logistical regression showed that AST was a more stable and capable index of indicating liver inflammation grade than ALT. Chen SS and other authors also reported similar findings (25,26).…”
Section: Discussionsupporting
confidence: 69%
“…We also constantly researched new indicators to predict liver inflammation with normal or near-normal alanine aminotransferase levels (23)(24)(25). Two types of serum indicators are used more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HBV replication and subsequent immune-mediated liver damage are the main key factors for disease progression. The inevitable progression of HBV infection to persistent or intermittent liver inflammation and fibrosis greatly increases the risk of progression to cirrhosis, Hepatocellular carcinoma (HCC) and end-stage liver disease [2]. Early and timely antiviral treatment can reverse liver fibrosis and early cirrhosis, thereby reducing the incidence of HCC [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that HBV replication and subsequent immune-mediated liver damage are the main key factors for disease progression. The inevitable progression of HBV infection to persistent or intermittent liver in ammation and brosis greatly increases the risk of progression to cirrhosis, Hepatocellular carcinoma (HCC) and end-stage liver disease [2]. Early and timely antiviral treatment can reverse liver brosis and early cirrhosis, thereby reducing the incidence of HCC [3,4] [5].Therefore, the main purpose of chronic hepatitis B virus (CHB) treatment is to inhibit HBV replication, reduce the occurrence of liver decompensation and prevent the progress of disease as soon as possible [1].…”
Section: Introductionmentioning
confidence: 99%